(untitled) (Global Journal of Human-Social Science, 2016)
Supply chain management (SCM) is the essential management philosophy and practice of materials, information, and finances where processes flow from supplier to manufacturer to wholesaler to retailer to consumer. This investigative study focus on a conceptual supply chain management (SCM) model for ready-made garments (RMG) industry of Bangladesh. The final goal of SCM is to convey information one group or individual to another. One group or individual should work together with its downstream customers and upstream suppliers to achieve supply chain goal. Communication helps to express employees to conquer their goals without any misinterpretation or misunderstanding. Current circumstances of SCM practice in garments industries have been revealed after questionnaire survey.